Best practices for accurate results using numerical solvers for microwave body screening - Martins, R. A.; Godinho, D.; Felício, J. M.; Savazzi, M.; Costa, J. R.; Conceição, R.; Fernandes, C. A. (2024 18th European Conference on Antennas and Propagation (EuCAP), 2024)
In this paper, we indicate best practices that should be observed when using numerical solvers for microwave body sensing. We show the impact of not minding these aspects in the case of microwave breast scanning, using the Computer Simulation Technology software tool. To this end we simulate a homogeneous breast with a 5-mm radius spherical tumor placed inside. The breast is illuminated by a broadband antenna that operates in the 2-6 GHz band. The scattering parameters are then processed to reconstruct the reflectivity map of the breast. The results highlight that the conclusions drawn from simulations may be misleading or meaningless when the solver type or positioning of model elements (body and antennas) are not carefully applied. This is particularly critical when considering more complex scenarios, such as inhomogeneous or multilayer body models.